Intraoperative evaluation of the resected bone margin in mandibular cancers using a trephine drill and frozen section analysis. Issue 4 (April 2023) - Hegde, P.; Gunishetty, V.; Shetty, V.; Shetty, U.; Abraham, S.; Bajjuri, S.
Abstract: The objective of this study was to evaluate the accuracy and feasibility of intraoperative frozen section analysis of samples harvested with a trephine drill from the bone resection margins to identify malignancy. Thirty-five patients who were diagnosed with locally advanced oral squamous cell carcinoma involving the mandible were included in this study. After tumour resection, bone samples were collected from the resection margin of the specimen using a trephine drill. Sampling yielded a cylindrical specimen of bony tissue that included both cortical and cancellous areas. A second sample was obtained from the area where bone invasion was evident; this was used as a positive control. Frozen section analysis was performed intraoperatively to check for malignancy. The sensitivity of this technique was found to be 81.8%, with specificity of 87.5%, a positive predictive value of 75%, negative predictive value of 91.3%, and accuracy of 85.7% when compared to standard histopathology as the gold standard. In conclusion, the evaluation of bone margins using the trephine drill technique and frozen section analysis proved to be fast and reliable.